Optimalisasi Penjualan Produk dan Manajemen Keuangan Melalui Pengelolaan Akuntansi dan Website Penjualan Online Pada Usaha Permen Tradisional “Soba Padu” - Mukhlisulfatih Latief; Moh. Syafri Tuloli; Lanto Miriatin Amali (DEDIKASI, 2020)
The partner of this Community Partnership Program (PKM) was a “Soba Padu” UKM. The objectives to be achieved in this service activity are (1) providing management / financial management assistance in making simple bookkeeping to partners and (2) providing promotional media and marketing / selling products in the form of a website as well as conducting training on the use of online sales websites to UKM partners "Soba Padu" in Bongomeme Village, Gorontalo District. Specific targets to be achieved are: (1) Availability of online sales website for UKM partners “Soba Padu” (2) There is simple bookkeeping produced by UKM  partners “Soba Padu”. To achieve these specific goals and targets the method used is through training and mentoring to UKM partners “Soba Padu” with lecture and demonstration techniques and practice. The end results of this Community Service activity are (1) the promotion of products produced by UKM through online sales websites, (2) increased sales of products from UKM "Soba Padu" and (3) creation of regular financial management in accordance with the principles correct financial management.